Angela Carter’s use of appropriation in the bloody chamber to return voices to the silenced and repressed female protagonists - Cheng, Yihui (2014)
A comparative analysis of Angela Carter's The Bloody Chamber against their original tales to highlight the issue on the silencing of women both in the society and within the text.